Emergent management for a Crashing patient with critical aortic stenosis in Hue Cardiovascular Center - Nguyen Tat Dung; Ho Anh Binh, Duong Dang Hoa, Pham Van Hue, Nguyen Huy Thong (Tạp chí Y học lâm sàng Bệnh viện Trung Ương Huế, 2020)
Critical aortic stenosis (AS) is the most problematic valvular disease encountered in the ICU. Patients with critical AS have a fixed cardiac output and cannot meaningfully increase cardiac output to meet the physiologic demands of critical illness. This article presents the case of a 53-year-old man with severe AS and pulmonary hypertension who developed hypotension while waiting for an elective aortic valve replacement. The article discusses practical considerations and emergent treatment for the hemodynamically unstable patient with critical AS.